Tinjauan Yuridis Terhadap Urgensi Amandemen Kelima UUD NRI 1945 - Baloch, Sania Mari; Sulastri, Sulastri; Rasji, Rasji (Peneliti.net, 2024)
Changing the constitution is a routine part of national governance. In Indonesian society, there are various views regarding the fifth amendment to the constitution. One perspective advocates for maintaining the fourth amendment, while another supports further amendment. A third group advocates for reverting to the original 1945 constitution. However, any amendments should be conducted meticulously, consistently, and comprehensively to enhance the Indonesian constitutional framework. The primary focus should be on returning sovereignty to the people by promoting participatory democracy and good governance.